Analysis of Tenurial Conflict of the Bunaken National Park (A Case Study of Mantehage Island) - Ronald , Ronald Junedie Aneng; Roland , Roland A Barkey; Muslim, Muslim Salam (Forestry Department, University of Muhammadiyah Makassar, 2021)
Bunaken National Park was designation based on the Decree of the Minister of Forestry Number: SK. 734 / Menhut-II / 2014. Boundary demarcation process of Bunaken National Park in Mantehage Island was rejected by the community due to land claims in the form of gardens and settlements. This study puposes to answer how the state of land cover and use of the Mantehage Island and how the tenurial conflicts. The analysis used is spatial analysis and Rapid Land Tenure Assessment (RaTA). The results indicate that land cover and use consisted of primary mangrove forests, dry land agriculture, mixed gardens, scrub, settlements and roads. Conflict occurred between the community and the Forest Area Boundary Committee for North Minahasa Regency because the community did not understand the boundary demarcation activitiess and regulations that could provide a solution to their land conflict problems. Conflict resolution mechanisms that can be taken is the settlement of third-party rights in boundary demarcation process, review of spatial planning and conservation partnerships.